1998
DOI: 10.1017/s0952523898151027
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive characteristics of subclasses of red–green P-cells in LGN of macaque

Abstract: We characterized the chromatic and temporal properties of a sample of 177 red-green parvocellular neurons in the LGN of Macaca nemestrina, using large-field stimuli modulated along different directions through a white point in color space. We examined differences among the properties of the four subclasses of red-green P-cells (on-and off-center, red and green center). The responses of off-center cells lag the stimulus more than do those of on-center cells. At low temporal frequencies, this causes the phase di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 33 publications
3
28
0
1
Order By: Relevance
“…These animals were also studied in the preceding paper (Lankheet et al, 1998), which describes the preparation and methods for recording from single units. That paper also provides details of visual stimulation and the methods used to find a neuron's chromatic signature.…”
Section: Methodsmentioning
confidence: 99%
“…These animals were also studied in the preceding paper (Lankheet et al, 1998), which describes the preparation and methods for recording from single units. That paper also provides details of visual stimulation and the methods used to find a neuron's chromatic signature.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several previous studies of retinal ganglion cells and neurons in the lateral geniculate nucleus (LGN) did not find more off-center than on-center cells or larger responses from off-center neurons (Krüger and Fischer, 1975;Kremers et al, 1993;Kaplan, 1997, 1999). Some studies even reported that on-center retinal ganglion cells had slightly stronger responses than offcenter cells (Lankheet et al, 1998;Chichilnisky and Kalmar, 2002), the opposite of the black vs white preference observed in V1 layer 2/3 and in human perception. Jin et al (2008) reported that the termination zones of off-center LGN afferents in cat V1 (area 17) were wider than those of on-center afferents.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the parvocellular neurons that map to central retina respond with opposite polarities when the retina is stimulated with long versus middle wavelength light (Wiesel and Hubel, 1966;De Valois et al, 1966;Gouras, 1968;De Monasterio, 1978;Derrington et al, 1984;Lankheet et al, 1998a). Recent studies strongly suggest that red-green spectral opponency results when the center of the receptive field of a parvocellular neuron gets exclusive input from either the long wavelength sensitive (L) or middle wavelength sensitive (M) cones while the concentric, spatially antagonistic receptive field surround gets exclusive input from the opposite cone type.…”
Section: Introductionmentioning
confidence: 99%